The clue in the trees : an Enchantment Lake mystery - Preus, Margi (University of Minnesota Press, 2017)
Francie plunges into her senior year of high school near Minnesota's Enchantment Lake, but when her long-lost brother, Theo, turns up, so does a dead body, and Francie is drawn into another mystery.